Sosiologi Hukum Maritim: Menuju Pembaruan Hukum yang Responsif bagi Masyarakat Pesisir Indonesia: Maritime Legal Sociology: Toward Legal Reform That Is Responsive to Indonesia’s Coastal Communities - Handi Pribadi (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2025)
The Indonesia, as an archipelagic nation, faces complex social, cultural, and economic challenges within the maritime space, which demand inclusive, responsive, and socially just legal formulations. This article examines the relevance of maritime legal norms to the social structure of coastal communities through a sociological perspective. The primary objective of this research is to analyze how a sociological approach to law can be used as a method for formulating maritime legal policies that are contextual and adaptive to the dynamics of coastal communities. This sociological approach demonstrates that good law is not only formally valid but also socially legitimate because it reflects local values, customary wisdom, and the just distribution of marine resources. The study's findings demonstrate that maritime legal reform must involve community participation, accommodate legal pluralism, and be based on the needs and social structure of coastal communities. By integrating formal norms and social practices, national maritime law can become an instrument for just, democratic, and sustainable social engineering.